Linking physicians' medical practice information needs, resources and barriers to job satisfaction: A moderated mediation model. Issue 6 (10th October 2016) - Kostagiolas, Petros; Gorezis, Panagiotis; Martzoukou, Konstantina; Deligeorgis, Dimitrios; Niakas, Dimitris
Abstract : Purpose: Medical doctors seek information in order to satisfy their demanding everyday work practices and professional development endeavours. Information seeking is a continuous goal-related process that has impact on how they perceive and experience their job. The purpose of this paper is to explore the association of doctors' awareness of medical practice information needs (MPIN), their frequency of using online information resources and the barriers they encountered during information seeking with their overall job satisfaction. More specifically, the research examined the mediating role of these information seeking related variables (information needs, online scholarly resources and information barriers) on doctors' overall job satisfaction. Design/methodology/approach: The study employed a questionnaire survey of 138 medical doctors working within the context of a University Hospital in Greece. The survey took place between February and March 2014. To test the hypotheses the authors conducted regression analysis, hierarchical moderated analysis and bootstrapping using SPSS macro developed by Preacher and colleagues. Findings: The statistical analysis found that higher awareness of MPIN had an indirect effect on doctors' overall job satisfaction when they used online information scholar resources. In addition, this indirect effect was contingent on information-related barriers. Originality/value: This study provides evidence for supporting the pivotal role of doctors' information seeking preferences in fostering job satisfaction. This is an understudied research area that deserves a unique focus particularly with the constantly expanding medical information space that has impact on doctors' medical practices and professional activities.